Negotiating Africanness : a response to Sylvester Ogbechie - Vorster, Stacey (My University, 2012)
Using an article written by Nigerian-‐born academic and critic, Sylvester Ogbechie, I consider the ways in which contemporary African art is constructed as a taxonomic category. Ogbechie’s article, ‘The Curator as Culture Broker’ (2010), is framed as a critical response to the practice of Nigerian-‐born African art curator Okwui Enwezor. I respond directly to the arguments and claims made in this article through a discussion of the ways in which Africanness and contemporaneity are negotiated in relation to organisational structures of time and space as well as through a consideration of two exhibitions curated by Enwezor: In/sight: African Photographers, 1940 to the Present (1996) and Snap Judgments: New Positions in African Photography (2006). My thesis is that the ways in which terms like contemporary African art are used in taxonomic endeavours often leads to oversimplification of our understandings of concepts like Africanness, like contemporaneity, and by extension like culture and history. My argument claims that Ogbechie’s position is bedevilled by a number of broad assertions that belie the complexity of the terrain and the discourse of contemporary African art.